Subhyoid ectopic thyroid with a solitary colloid nodule in a 10-year-old girl: a rare diagnostic entity - Chawla, Meghna; Naik, Ajay; Naik, Prashant (International Surgery Journal, 2018)
Ectopic thyroid is a rare clinical entity, of which its presence in a subhyoid location is uncommon. It is equally rare to find a solitary thyroid nodule in the paediatric age group. We report a case of subhyoid ectopic thyroid in a 10-year-old girl, and its course over a span of 3 years. It was associated with a solitary colloid nodule, which eventually became symptomatic and did not respond to suppressive levothyroxine therapy. Hence surgical excision was done, and the child was put on replacement doses of levothyroxine.